Kesejahteraan Psikologis dan Praktik Pendidikan Positif Sebagai Landasan Kesehatan Mental Mahasiswa Di Perguruan Tinggi Pada Era Digital - Diki Arisandi; Seri Hartati; Destita Mutiara (EL-EMIR Institute, 2025)
Student mental health has become a strategic issue in higher education as the learning environment becomes increasingly digitalized and dynamic. Universities are no longer solely focused on academic achievement but are also required to build a learning ecosystem that sustainably supports student psychological well-being. This study aims to analyze the role of psychological well-being and positive education practices as the foundation for strengthening student mental health. Unlike previous studies, which generally examine these two aspects separately, this study integrates psychological well-being and positive education into a single empirical model to explain student mental health in the context of Indonesian higher education. The study used a quantitative approach with an ex post facto design. Participants were recruited using a Likert-scale questionnaire with 397 active students at various public and private universities in Pekanbaru City. Psychological well-being was measured through the dimensions of autonomy, personal growth, purpose in life, and positive relationships, while positive education was measured using the PERMA framework. Multiple linear regression analysis showed that psychological well-being significantly influenced student mental health (β = 0.52; p < 0.001), and positive educational practices also contributed significantly (β = 0.47; p < 0.001), with both variables simultaneously explaining 48% of the variation in student mental health. These findings emphasize the importance of a promotive approach that integrates strengthening student psychological capacity and positive educational practices as a systematic strategy for building mental resilience in higher education in the current digital era.